Methylation analysis of a marsupial X-linked CpG island by bisulfite genomic sequencing. - Loebel, D A; Johnston, P G (Genome Research, 1996)
Paternal X chromosome inactivation occurs in rodent extraembryonic membranes and in all tissues of marsupials. Methylation of CpG islands occurs on the inactive X in eutherians and is considered to be a stabilizing mechanism. The only previous study of a marsupial X-linked CpG island was of the G6PD gene of the Virginia opossum, in which the paternally derived allele is not completely repressed. We have cloned the 5' end of the G6PD gene from an Australian marsupial, the common wallaroo, and sequenced the associated CpG island. The paternally derived G6PD allele is completely repressed in tissues of this species. Methylation analysis using HpaII and Cfol restriction enzymes and bisulfite genomic sequencing of 47 CpG dinucleotides in a 613-bp region reveals hypomethylation of male and female DNA from tissues, cultured fibroblasts (in which the paternal allele is partially expressed) and sperm. This suggests that methylation of CpG islands is not required for maintenance of X inactivation in marsupials even where repression of the paternal allele is complete.